Mechanization takes command : a contribution to anonymous history - Giedion, Siegfried, 1888-1968 (New York : Norton, 1969)
Anonymous history - Springs of mechanizaton - Means of mechanization (locks, assembly line) - Mechanization encounters the organic (agriculture, bread making, meat production) - Mechanization encounters human surroundings (furniture) - Mechanization encounters the household (kitchen, laundering, refrigeration) - Mechanization of the bath - Conclusion
First published in 1948, Mechanization Takes Command is an examination of mechanization and its effects on everyday life. A monumental figure in the field of architectural history, Sigfried Giedion traces the evolution and resulting philosophical implications of such disparate innovations as the slaughterhouse, the Yale lock, the assembly line, tractors, ovens, and “comfort” as defined by advancements in furniture design. A groundbreaking text when originally published, Giedion’s pioneering work remains an important contribution to architecture, philosophy, and technology studies.